(3QSGdI aj JMbjb hVY cGOs - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO dhdjg hGdUdGI Ydi fHjg CeG HYO (B: (3agPg QSGdI ai JMbjb hVY cGO hJhVjM WQjb GSJYeGdg Ef cGO ai CUd GdhVY jYfi bQH s
(3BNQgG (B:s
(3abGe QShd Gddg Udi Gddg Ydjg hSde jUdi MJi de jcO jQcY Ke QcY ade jcO jQaY QCSg Ke QaY QCSg hGdMOjK HJeGeg ePchQ ajeG Cdag GdJQePi ai TeGFd GdfHi Ydjg GdSdGe JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI (B11s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9237) s
Keywords: (3GddZIs